Dental Malocclusion and Its Relation to the Podal System - Cabrera-Domínguez, María E.; Domínguez-Reyes, Antonia; Pabón-Carrasco, Manuel; Pérez-Belloso, Ana J.; Coheña-Jiménez, Manuel; Galán-González, Antonio F. (Frontiers in Pediatrics, 2021)
Introduction This study analyzes the possibility that Stomatognathic and Postural systems are related by muscle chains. Malocclusion may influence the posture, contact between the foot and the ground, center of mass, footprint or vice-versa. Objective. To verify whether there is a relationship between dental occlusion and podal system. Materials and methods. A cross-cutting, descriptive study was carried out on 409 children (222 boys and 187 girls) between 8 and 14 years old. Dental occlusion was assessed on the sagittal plane (Angle's classification) the contact between the foot and the ground and the center of mass were evaluated using a stabilometric platform. Results. There was a statistically significant relationship between the plantigrade phase, the con-tact surface area and center of gravity. There was a prevalence of molar and canine Angle's class II malocclusion. In molar class II, an anterior center of gravity was predominant, in class I it was centered and in class III, it was posterior. There was significant correlation between malocclusions and the FPI (foot posture index) of the left foot and the height of the scaphoid in the right foot (P <0.001). Discussion. Some authors agree with our results. There is still much uncertainty in terms of showing a relationship between both systems. In addition, there is scarce scientific evidence on the topic. Conclusions Some kind of relationship between the two systems has been proven.Studies that evalu-ate a group of subjects in a longitudinal manner are necessary to enable the changes taking place in both systems to be defined.